Вы находитесь на странице: 1из 4

Math 104, Solution to Homework 1

Instructor: Guoliang Wu

1.2 Prove 3 + 11 + · · · + (8n − 5) = 4n2 − n for all natural numbers n.

Solution: (1) When n = 1, the assertion holds since 3 = 4·12 −1.
(2) Suppose 3 + 11 + · · · + (8n − 5) = 4n2 − n, we want to show
that

Thus, by induction, we have proved the claim.

1.3 Prove 13 +23 +· · ·+n3 = (1+2+· · ·+n)2 for all natural numbers n.
Solution: (1) When n = 1, the assertion holds since 13 = 1 = 12 .
(2) Suppose 13 + 23 + · · · + n3 = (1 + 2 + · · · + n)2 , we want to show
that

13 + 23 + · · · + n3 + (n + 1)3 = [1 + 2 + · · · + n + (n + 1)]2 .

The left hand side equals (by induction assumption)

(1 + 2 + · · · + n)2 + (n + 1)3 ,

and the right hand side equals (using the formula for (a + b)2 =

1
...)

(1 + 2 + · · · + n)2 + 2(1 + 2 + · · · + n)(n + 1) + (n + 1)2

n(n + 1)
=(1 + 2 + · · · + n)2 + 2 (n + 1) + (n + 1)2 (Here we use the formula
2
n(n+1)
1 + 2 + ··· + n = 2 , which itself can be prove by induction.)
=(1 + 2 + · · · + n)2 + n(n + 1)2 + (n + 1)2
=(1 + 2 + · · · + n)2 + (n + 1)3 .

Thus, we obtain the desired equality. By induction, we have

proved the claim.

Proof. (1) When n = 1, the assertion holds since 11 − 4 = 7 is

divisible by 7.
(2) Suppose that 11n − 4n is divisible by 7, we want to show that
11n+1 − 4n+1 is also divisible by 7.

11n+1 − 4n+1 = 11(11n ) − 4(4n ) = 11(11n − 4n ) + 11(4n ) − 4(4n )

= 11(11n − 4n ) + 7(4n ).

The first term is a divisible by 7 since 11n −4n is, and the second
term 7(4n ) is clearly a multiple of 7. Therefore, 11n+1 − 4n+1 is
also divisible by 7.
By induction, we proved the claim.

n.

Proof. (1) When n = 1, the assertion holds since 71 − 6 − 1 = 0

is divisible by 7.
(2) Suppose that 7n − 6n − 1 is divisible by 36, we want to show
that 7n+1 − 6(n + 1) − 1 is divisible by 36.

7n+1 − 6(n + 1) − 1 = 7(7n ) − 6(n + 1) − 1

= 7(7n − 6n − 1) + 7(6n + 1) − 6(n + 1) − 1
= 7(7n − 6n − 1) + 36n.

2
The first term is a divisible by 36 since 7n − 6n − 1 is, and
the second term 36n is clearly a multiple of 36. Therefore,
7n+1 − 6(n + 1) − 1 is divisible by 36.
By induction, we proved the claim.

1.9 (a) Decide for which integers the inequality 2n > n2 is true.
(b) Prove you claim in (a) by mathematical induction.
Solution: (a) We check that when n = 2, equality holds. For
n = 3, 23 = 8 < 32 = 9. When n = 2, equality holds again. For
n = 5, 6, · · · , 2n > n2 holds since 25 = 32 > 52 = 25, 26 = 64 > 62 =
36, etc. We may guess that 2n > n2 is true for n ≥ 5.
(b) We use mathematical induction (or rather, a slight varia-
tion. See Exercise 1.8 in the textbook.) to prove our assertion
in (a).
(1) When n = 5, we have checked that 2n > n2 is true.
(2) Suppose 2n > n2 for some n ≥ 5, we need to show that
2n+1 > (n + 1)2 is also true. Observe that

2n+1 = 2(2n ) > 2n2 = n2 + n2 = n2 + 2n + 1 + (n2 − 2n − 1)

= (n + 1)2 + (n − 1)2 − 2 ≥ (n + 1)2 + 42 − 2 > (n + 1)2 .

2.3 Show that (2 + 2)1/2 does not represent a rational number.
√ √
Solution: Denote by a = (2 + 2)1/2 . Then a2 = 2 + 2 and
(a2 − 2)2 = 2. Thus, a is a root of the equation

a4 − 4a2 + 2 = 0.

By Rational Zeros Theorem, the only possible rational roots

of this equation are ±1, ±2.
√ We check that none of them is a
root. Therefore, a = (2 + 2) 1/2 does not represent a rational
number.

2.5 Show that (3 + 2)2/3 does not√represent a rational number.√
Solution:
√ Denote by b = (3 + 2)2/3 . Then b3 = (3 + 2)2 =
11 + 6 2 and (b3 − 11)2 = 72. Thus, b is a root of the equation

b6 − 22b3 + 49 = 0.

3
By Rational Zeros Theorem, the only possible rational roots of
this equation are ±1, ±7, ±49.
√ We check that none of them is
a root. Therefore, b = (3 + 2)2/3 does not represent a rational
number.

Extra. If r ∈ Q, r 6= 0, and x is irrational, prove that r + x and rx are

irrational.
Solution: We can prove the claim by contradiction. First, we
know r 6= 0 is a rational number, which can be written as mn
where m, n ∈ Z and m, n 6= 0.
1) Suppose r + x is also rational, then it can be written as
r + x = pq , with p, q integers and q 6= 0. Then

p m pn − qm
x = (r + x) − r = − =
q n qn

is rational since pn − qm and qn are both integers and qn 6= 0.

This is a contradiction to the assumption that x is irrational,
and hence r + x cannot be rational.
2) Similarly, suppose rx is rational, then we can write it as
0
rx = pq0 with p0 , q 0 integers and q 0 6= 0. Then
 0  
p m p0 n
x = (rx)/r = 0
/ =
q n qm

is rational since p0 n and qm are both integers and qm 6= 0. This

is again a contradiction and hence rx cannot be rational.

Нижнее меню

Получите наши бесплатные приложения

Авторское право © 2021 Scribd Inc.